Optimizing the use of sewing materials to maximize production output - Rakhmawati, Fibri; Rifki, Mhd Ikhsan; Husein, Ismail; Cipta, Hendra; Lubis, Riri Syafitri; Sari, Rina Filia (Civiliza Publishing, 2025)
This Community Service Program aims to optimize the use of sewing materials to maximize production output at Rumah Jahit Nila through the application of a linear programming model in the allocation and use of sewing materials in planning and maximizing production output. The implementation methods include mapping processes and data requirements and formulating a linear programming model relevant to the scale of Nila Sewing House MSMEs, as well as training and live demonstrations using QM as software to determine optimization solutions. The evaluation was conducted on 15 participants using a 1–4 Likert scale instrument with four assessment indicators, namely, training content, presenter's subject-matter expertise, event facilities, and benefits of the program. Descriptive analysis showed an overall average of 3.43 on a scale of 4, with a percentage level of 85.8%, which is in the Very Good category. In order, the indicator achievements are Presenter’s Subject-Matter Expertise = 3.53 (88.33%), Benefits of the Program = 3.47 ( 86.67%), Training Content = 3.40 (85.00%), and Event Facilities = 3.33 (83.33%). These results confirm that the competence of the speakers and the relevance of the benefits are the main strengths, while the content and facilities of the activities are areas for priority improvement. This program has successfully improved participants' technical capacity in modeling and implementing linear program-based raw material optimization, while also providing a foundation for operational implementation to reduce waste and increase throughput.